Pengembangan Model Perangkat Ajar Berbasis Animasi: Studi Kasus Mata Ajar Biologi pada SMP Yaspia dan SMK Bina Manajemen Cakung Jakarta Timur - Pujadi, Tri; Harisno, Harisno (Bina Nusantara University, 2013)
Use of the Internet at schools grows advanced. Therefore, teachers need to learn the use of technology in creating good teaching materials (learning objects) such as animation-based materials. Those materials will result will in a component in a learning system that allows students to interactively learn and evaluate themselves against the subject mastery. A tool for creating such an animated material like Powerpoint produces presentations enhanced with audio and video that allows students to comprehend the lessons more easily. The model system uses interactive multimedia system design and development with the following phases: (1) system requirements, (2) design considerations, (3) implementation, (4) evaluation. While user interface design principles uses eight golden rules of interface design. As a test case, selected Biology at Yaspia junior high school and Bina Management vocational school. From the results it can be concluded that this application module can support students in obtaining the required data completeness. The tutorials are quite sufficient to facilitate students in understanding the material.